Redeeming Humanity: Materiality and Spirituality in Bernard Shaw’s Major Barbara - Pokharel, Bishnu Prasad (English Language Teaching Perspectives, 2024)
George Bernard Shaw’s Major Barbara deals with the conflict between materialistic forces and spiritual values and the victory of the former over the latter to infuse the materialistic power of the contemporary society. The implication of material possession ultimately leads to the transformation of ethics and ideology to commodification. Culler, Foley, and Oakley’s materialism and Swami Avdhesh Anand Giri’ and Sir Aurobindo’s spiritualism are the theoretical underpinning of the study to analyze the text. The material society reasons for physical, and monetary well-being, but spirituality prioritizes the community’s well-being through psychic devotedness. Spiritualism is the higher order of rational that values the greater good of the society for the welfare of the humanity. The consumer culture generates condition to accept the incentives from the sources of unethical and illegal work. The initial clash and ultimate resolution between Andrew Undershaft and Major Barbara indicates the victory of consumer culture over spiritual values. The images created by Undershaft about the army highlight poverty, misery, feebleness, and hunger but Major Barbara hardly succeeds in defeating these issues. This study questions about the knowledge dissemination in the institutionalized societies showing materialistic forces stronger than spiritual values and the need for redeeming the humanity. The devaluation of the essence of the social welfare working under the shadows of commercial notion blemishes the morality. It raises the question about ethics, sophisticated attachment, and monetary orientation. This paper concludes that harmony in society is possible through redeeming humanity having spiritual feeling in all aspects of existence.